Malformação congênita relacionada à exposição materna aos agrotóxicos - Groth, Bruna Rayeli (2022)
ABSTRACT: Introdução: Intensive agriculture is on the rise in Brazil, as is the consumption of pesticides. The exposure of women to certain groups of pesticides has been associated with adverse effects during the gestational period, such as congenital malformation. Objective: To analyze the occurrence of congenital malformation related to maternal exposure to pesticides, in Mato Grosso, Brazil. Method: This is an epidemiological study of spatial distribution and temporal trend, based on records of live births with congenital malformations in the municipalities of the State of Mato Grosso. Soybean, corn and cotton crops were selected because they are the largest grain plantations in the state. The information was obtained by the Live Births Information System of the Ministry of Health and via the database of the National System of Notifiable Diseases of Mato Grosso, of the Municipal Agricultural Production of the Automatic Recovery System of the Brazilian Institute of Geography and Statistics. The variables related to geographic distribution were considered: mesoregion, municipality of maternal residence, area planted or intended for harvesting, in hectares, of temporary and permanent crops; as well as those related to maternal exposure to pesticides: live births with congenital malformation and number of liters of pesticides used in the municipalities of the State in 2010 and 2019. The variables related to the time series study were those regarding maternal and newborn characteristics -born in the period from 2008 to 2018. For the elaboration of the spatial distribution, the ArcGis 10.2 software was used and for the trend analysis, the Prais-Winsten regression method, adopting a significance level of 5%. Results: There is a reduction in the consumption of liters of agrochemicals in 2019 when compared to 2010. The incidence rate was 7.8 cases of congenital malformation per thousand live births in the northern mesoregion in 2010 and 7.2 cases in the southeastern mesoregion in 2019. The general annual trend of congenital malformation cases proved to be stationary, with a higher occurrence in male urinary tract malformations, weighing more than 2,500 grams, gestational age greater than 37 weeks and Apgar score greater than 07, born to mothers over 25 years of age and with a higher level of education. Conclusion: The highest occurrence of congenital malformations was recorded in the mesoregions that had the highest consumption of pesticides in the state. This finding suggests that maternal exposure may be related to a greater chance of children being born with some type of congenital malformation in regions with greater permanent and temporary cultivation of soybeans, corn and cotton in municipalities in the state. The higher the gestational age and maternal education, the greater the occurrence of congenital malformations, with an increasing annual trend in cases. Further studies on this topic are suggested, based on the findings of this study, for the purpose of strengthening strategies to prevent the disease.